Onkwehón:we Spirituality and the Reconciliatory Journey in Canadian Education - Deer, Frank (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
In recent decades, Onkwehón:we (Indigenous) education has been a burgeoning area of study and practice in primary, secondary, and post-secondary schools in Canada. One of the more significant contributions to this growth in recent years has been the findings of the Truth and Reconciliation Commission of Canada and its 94 Calls to Action. Central to the journey of reconciliation is understanding of the experiences of Onkwehón:we people and their perspectives on various things. Given that spirituality and associated ceremonial observances are important to many Onkwehón:we communities and have been explored in a number of schools and universities, their inclusion in academic and non-academic school programming merits exploration. This essay explores the importance of Onkwehón:we spirituality, its role in the reconciliatory journey, and the value of enabling schools to partner with Indigenous peoples to aid in its dissemination.